LABORATORY COMPARISON OF EVA BASED RESIN AND SBS MODIFIED BITUMINOUS BINDER - Furtana, Beyza; Yalçın, Erkut; Kök, Baha Vural; Yılmaz, Mehmet Bırhan (My University, 2020)
Although the bitumen used too few in the asphalt concrete it is significantly liable to the performance of pavement. For this reason bitumen is frequently modified in order to enhance the performance of asphalt mixtures. Stiren butadiyen stiren (SBS) is a widely used polymer modifier for asphalt binders to improve the performance properties of hot mix asphalt. (SBS) is nearly indispensable when the binder properties do not satisfy the specification requirements under hot service temperatures. In this study the performance of an alternative additive named as ethylene vinyl acetate (EVA) based resin (EBR) to SBS was investigated. The SBS contents were kept constant at 3% and EBR contents were 2%, 3% 4% and 5% by weight of base bitumen. Modified binders were produced by mixing a 50/70 penetration grade base bitumen with SBS and EBR. Penetration, softeningpoint, rotational viscometer tests were conducted to base and modified binders and results were compared with each other. In conclusion it was determined that EBR content have to be more than 3% in order to obtain the same performance with 3% SBS modification. 3% EBR modification gave satisfactory performance in terms of temperature sensitivity, high temperatureresistance and workability.
Keywords: Malzeme Bilimleri; Özellik ve Test; İnşaat ve Yapı Teknolojisi; Polimer Bilimi